2013
DOI: 10.1002/mc.22015
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling regulates drug sensitivity by targeting ABC transporters ABCB1 and ABCG2 in epithelial ovarian cancer

Abstract: A major challenge of successful chemotherapy in ovarian cancer is overcoming intrinsic or acquired multi-drug resistance caused by active drug efflux mediated by ATP-binding cassette (ABC) transporters. Regulation of these transporters in ovarian cancer is poorly understood. We have found that abnormal expression of the hedgehog (Hh) signaling pathway transcription factor Gli1 is involved in the regulation of ABC transporters ABCB1 and ABCG2 in ovarian cancer. Hh is a known regulator of cancer cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 34 publications
2
70
0
2
Order By: Relevance
“…26 These findings are further supported by the observation that ABCB1 and ABCG2 promoter regions have the consensus sequence of Gli-binding site, and Gli-1 directly bound to the consensus GACCACCCA-like motif located in the promoter regions of ABCB1 and ABCG2 to regulate their transcription in B-cell lymphoma and ovarian cancer cells. 27,28 However, our results demonstrate that ABCC1 was highly expressed in Huh-7-DN and Huh-7-trans cells; in Figure 7 The effects of LDE225 and itraconazole on expression of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation. Huh-7-DN cells were exposed to LDE225 or itraconazole at various concentrations as indicated for 24 h. mRNA levels of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation were determined by quantitative RT-PCR, using untreated Huh-7 cells as a control.…”
Section: Discussionmentioning
confidence: 62%
“…26 These findings are further supported by the observation that ABCB1 and ABCG2 promoter regions have the consensus sequence of Gli-binding site, and Gli-1 directly bound to the consensus GACCACCCA-like motif located in the promoter regions of ABCB1 and ABCG2 to regulate their transcription in B-cell lymphoma and ovarian cancer cells. 27,28 However, our results demonstrate that ABCC1 was highly expressed in Huh-7-DN and Huh-7-trans cells; in Figure 7 The effects of LDE225 and itraconazole on expression of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation. Huh-7-DN cells were exposed to LDE225 or itraconazole at various concentrations as indicated for 24 h. mRNA levels of Gli-1, Gli-2, and ABCC1 in Huh-7-DN subpopulation were determined by quantitative RT-PCR, using untreated Huh-7 cells as a control.…”
Section: Discussionmentioning
confidence: 62%
“…The P-gp protein encoded by ABCB1 regulates the drug cumulative effect in tumour cells and eventually participates in the multidrug resistance process by being involved in drug transport across the membrane and in membrane stability maintenance (57); ABCG2 possesses ATP activity and is involved in biological processes, including drug transport and cell membrane stability (58). Chen et al (59) observed that ABCB1 and ABCG2 are involved in ovarian cancer drug resistance through the transcription factor Gli of the Hh signalling pathway. Gli expression inhibition may reduce ABCB1 and ABCG2 gene expression levels and strengthen the sensitivity of ovarian cancer to chemotherapy.…”
Section: Protein Interaction Analysis For 26 Methylated Genesmentioning
confidence: 99%
“…Сигнальный путь HH через транскрипционный фактор GLI1 способен влиять на экспрессию генов ABC переносчиков ABCG2, MDR1, MRP1 и генов MVP и MGMT, принимающих участие в формировании химиорезистентности [53,90,91]. Показано, что GLI1 влияет на экспрессию MGMT, связываясь с GLI1-связывающим сайтом в его промотере [92].…”
Section: влияние на процессы химиорезистентностиunclassified
“…Химиопрепараты и циклопамин значительно увеличивали гибель клеток и уровень апоптоза [53]. Аналогичные данные были продемонстрированы при ингибировании GLI1 в культуре клеток рака яичников [91].…”
Section: влияние на процессы химиорезистентностиunclassified